Detection of Non-Helmet Riders and Triple riders - N.Srinu , R.Ramanjaneyachary, M.Ravi Teja, G.Sandeep , B.Likhita , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
It is difficult to enforce traffic regulations in India due to the country's large population. Despite the clear risks, many motorcyclists still opt out of wearing helmets. It takes a lot of time for the traffic police to monitor all the vehicles on the road. Many of the busier areas have installed cctvs for added security. The infrastructure to expedite the surveillance and monitoring of motorcyclists already exists. The authors of this investigation suggest a method for tracking down the VIN of every motorcycle being operated by an unprotected rider and for identifying those who are tripling up without helmets. The YOLO (You Only Look Once) method is used to determine the identity of the rider, the helmet, and the bike. Based on the COCO dataset, YOLO can distinguish between 80 distinct classes. YOLO was trained using data from sources such as pictures of helmets and licence plate information. The results from using this method are superb